Experimental Investigation of Exterior Mechanbical Precast Beam Column Connections using Internal Dissipators under Seismic Loading - K. Thulasirajan; Revathi (Electronic Journal of Structural Engineering, 2018)
This paper investigates the development and testing of the proposed one-third scaled precast beam column specimens using cleat angle and unbonded threaded rod connection (internal dissipator) under reverse cyclic loading. One monolithic specimen for reference and two precast specimens were studied. The parameters considered in the precast specimens were the presence of stiffener and the action of cement grouting in the predetermined gap of the beam column interface region. The load and displacement were measured for the cyclic loading and thereby strength, hysteretic behaviour, energy dissipation, stiffness, ductility and stiffness degradation were computed and compared. The experimental results showed that the performance of monolithic specimen was superior to precast specimens. The performance of precast specimen with cleat angle and stiffener was found to be superior to precast specimen without stiffener.